Journalism in Digital Native Media: Beyond Technological Determinism - Berta García-Orosa; Xosé López-García; Jorge Vázquez-Herrero (Media and Communication, 2020)
This article reflects on the conceptualisation and practise of journalism in European digital native media. The way news is produced and consumed in the digital era knocks down the boundaries that once divided professionals, citizens, and activists. At the same time, significant changes highlighted in recent studies call for a new theoretical and practical approach that goes beyond the dominant perspective of technological determinism. In relation with previous research, we have selected innovative digital media platforms (De Correspondent, Heidi.news, Eldiario.es, IlPost, Mediapart, and Observador), and we have analysed the types of journalism they set out to produce, as gleaned from their public-facing communications and interviews with the platforms’ founders and editors, comparing their stated goals with the journalism they produce and, lastly, we commented on changes in journalism. Digital native media explore renewed fields for journalism. The present analysis allows identifying the emergence of a series of trends in digital native media, which show a coexistence of traditional and new principles. Beyond the technological impact, the new media respond to the needs of society by incorporating the citizen as a reason for its purpose and as a collaborator in production processes. On the other hand, new players and an updated role of journalists come into play with innovative proposals designed for the current multiplatform and mobile scenario.